Aortic stiffness and blood pressure variability in young people: A multimodality investigation of central and peripheral vasculature - Boardman, H; Lewandowski, A; Lazdam, M; Kenworthy, Y; Whitworth, P; Zwager, C; Francis, J; Aye, C; Williamson, W; Neubauer, S; Leeson, P (Lippincott, Williams & Wilkins, 2017)
Introduction – Increased blood pressure variability is a cardiovascular risk marker for young individuals and may relate to the ability of their aorta to buffer cardiac output. We used a multimodality approach to determine relations between central and peripheral arterial stiffness and blood pressure variability. Methods – We studied 152 adults (mean age of 31 years) who had blood pressure variability measures based on standard deviation (SD) of awake ambulatory blood pressures, 24hr weighted SD and average real variability (ARV). Global and regional aortic distensibility was measured by cardiovascular magnetic resonance, arterial stiffness by Cardio-Ankle Vascular Index (CAVI), and pulse wave velocity (PWV) by SphygmoCor (carotid-femoral) and Vicorder (brachial-femoral). Results – In young people, free from overt cardiovascular disease, all indices of systolic (SBP) and diastolic blood pressure (DBP) variability correlated with aortic distensibility (global aortic distensibility vs awake SBP SD: r=-0.39, p<0.001; SBP ARV: r=-0.34, p<0.001; weighted 24hr SBP SD: r=-0.42, p<0.001). CAVI, which closely associated with aortic distensibility, also related to DBP variability, as well as awake SBP SD ((r=0.19, p<0.05) and weighted 24hr SBP SD (r=0.24, p<0.01), with a trend for SBP ARV (r=0.17, p=0.06). In contrast, associations with PWV were only between carotid-femoral PWV and weighted SD of SBP (r=0.20, p=0.03) as well as weighted and ARV of DBP. Conclusions – Greater blood pressure variability in young people relates to increases in central aortic stiffness, strategies to measure and protect aortic function from a young age may be important to reduce cardiovascular risk.